Monitoring Mitochondrial Partial Oxygen Pressure During Cardiac Arrest and Extracorporeal Cardiopulmonary Resuscitation. An Experimental Pilot Study in a Pig Model - Mandigers, Loes; Pooth, Jan-Steffen; Wefers Bettink, Mark A.; Uil, Corstiaan A. den; Damjanovic, Domagoj; Mik, Egbert G.; Brixius, Sam; Gommers, Diederik; Trummer, Georg; dos Reis Miranda, Dinis (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Ischemia and reperfusion are crucial in determining the outcome after cardiac arrest and can be influenced by extracorporeal cardiopulmonary resuscitation (ECPR). The effect of ECPR on the availability and level of oxygen in mitochondria remains unknown. The aim of this study was to find out if skin mitochondrial partial oxygen pressure (mitoPO2) measurements in cardiac arrest and ECPR are feasible and to investigate its course. Materials and methods: We performed a feasibility test to determine if skin mitoPO2 measurements in a pig are possible. Next, we aimed to measure skin mitoPO2 in ten experimental pigs. Measurements were performed using a cellular oxygen metabolism measurement monitor (COMET), at baseline, during cardiac arrest, and during ECPR using the controlled integrated resuscitation device (CIRD). Results: The feasibility test showed continuous mitoPO2 values. Nine experimental pigs could be measured. Measurements in six experimental pigs succeeded. Our results showed a delay until the initial spike of mitoPO2 after ECPR initiation in all six experimental tests. In two experiments (33%) mitoPO2 remained present after the initial spike. A correlation of mitoPO2 with mean arterial pressure (MAP) and arterial partial oxygen pressure measured by CIRD (CIRD-PaO2) seemed not present. One of the experimental pigs survived. Conclusions: This experimental pilot study shows that continuous measurements of skin mitoPO2 in pigs treated with ECPR are feasible. The delay in initial mitoPO2 and discrepancy of mitoPO2 and MAP in our small sample study could point to the possible value of additional measurements besides MAP to monitor the quality of tissue perfusion during cardiac arrest and ECPR.